COMPRESSIVE STRENGTH BEHAVIOUR OF CONCRETE PRODUCED USING OKIGWE RED LUMP STONE AS COARSE AGGREGATE - CHIOMA TEMITOPE GLORIA AWODIJI; CHINEDU PAUL EZEGO; DAVIS OGBONNA ONWUKA; STANLEY EMEKA IWUOHA (Journal of Engineering Studies and Research)
This study was carried out in order to ascertain if the Okigwe red lump stone, found in South-eastern Nigeria, could be used as coarse aggregate in making structural concrete. The maximum compressive strength values, obtained at 28 days for red lump stone concrete were 13.72 N/mm2 at w/c ratio of 0.53 for mix ratio 1:2:4 and 8.74 N/mm2 for mix ratio 1:3:6, at w/c ratio of 0.55. These values were not up to 20 N/mm2 which is the ACI 318 (1995) recommendation for structural concrete. Therefore, Okigwe red lump stone must not be used in making structural concrete using mixes 1:2:4 and 1:3:6.